Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1111/mpp.12142
|View full text |Cite
|
Sign up to set email alerts
|

The movement protein (NSm) of Tomato spotted wilt virus is the avirulence determinant in the tomato Sw‐5 gene‐based resistance

Abstract: The avirulence determinant triggering the resistance conferred by the tomato gene Sw-5 against Tomato spotted wilt virus (TSWV) is still unresolved. Sequence comparison showed two substitutions (C118Y and T120N) in the movement protein NSm present only in TSWV resistance-breaking (RB) isolates. In this work, transient expression of NSm of three TSWV isolates [RB1 (T120N), RB2 (C118Y) and non-resistance-breaking (NRB)] in Nicotiana benthamiana expressing Sw-5 showed a hypersensitive response (HR) only with NRB.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
70
0
12

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(83 citation statements)
references
References 73 publications
1
70
0
12
Order By: Relevance
“…Lopez et al (2011) suggested that amino-acid substitution at position 118 (C118Y) or 120 (T120N) in the TSWV NSm might result in breaking of the Sw-5-mediated resistance in tomato. , Peiró et al (2014 demonstrated that the presence of a tyrosine at position 118 or an asparagine at position 120 in NSm abolished the Sw-5-mediated HR. To further analyse these two amino acids, a single amino-acid substitution (C118Y or T120N) was introduced into the PD-nontargeting NSm A54-56 mutant.…”
Section: Tomato Spotted Wilt Virus (Tswv) Is the Type Species Ofmentioning
confidence: 99%
See 2 more Smart Citations
“…Lopez et al (2011) suggested that amino-acid substitution at position 118 (C118Y) or 120 (T120N) in the TSWV NSm might result in breaking of the Sw-5-mediated resistance in tomato. , Peiró et al (2014 demonstrated that the presence of a tyrosine at position 118 or an asparagine at position 120 in NSm abolished the Sw-5-mediated HR. To further analyse these two amino acids, a single amino-acid substitution (C118Y or T120N) was introduced into the PD-nontargeting NSm A54-56 mutant.…”
Section: Tomato Spotted Wilt Virus (Tswv) Is the Type Species Ofmentioning
confidence: 99%
“…This Sw-5b resistance gene has been cloned and shown to contain a coiled-coil, a central nucleotide-binding site (NBS), C-terminal leucine-rich repeats (LRRs), and an extra N-terminal domain (Brommonschenkel et al, 2000;Spassova et al, 2001). The avirulence (Avr) factor of the tomato Sw-5b-resistance protein has been determined as the nonstructural movement protein NSm of TSWV (Hallwass et al, 2014;Lopez et al, 2011;Peiró et al, 2014). Transient expression of the NSm protein in leaves of Sw-5 tomato or Sw-5 transgenic Nicotiana benthamiana resulted in a hypersensitive response (HR) (Hallwass et al, 2014;Peiró et al, 2014).…”
Section: Tomato Spotted Wilt Virus (Tswv) Is the Type Species Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Sw-5 is responsible of triggering Hypersensitive Response (HR) in sites of infections impeding systemic infections in the host. Sw-5 targeted the pathogen avirulence protein (NSm) (Peiro et al, 2014). Although five paralogues are present in plant genomes, it was shown that only one is necessary and sufficient to induce resistance against TSWV (Spassova et al, 2001).…”
Section: Characteristic Of Tomato Spotted Wilt Virus (Tswv)mentioning
confidence: 99%
“…The ORF located in the complementary viral M RNA encodes the precursor of the Gn and Gc glycoproteins that are localized in the viral particle envelope and that are important for tospovirus transmission mediated by thrips in a circulative and propagative mode Sin et al, 2005). The ORF in the viral RNA sense encodes a non-structural protein (NSm) involved in the short distance (cell-to-cell) and systemic movements ) and, more recently, proved to work as an avirulence determinant Peiro et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%